(untitled) (Cadernos de Sociomuseologia, 2020)
The present research deals with Museology, Memory and Education, and aims to recognize how people appropriate their memories and how this contributes to the development of their critical awareness about the world. In a theoretical approach examines the influence of the thought of the Brazilian educator, Paulo Freire, as a significant reference to the two fields, with emphasis on their reformulations, namely Social Museology and Sociopedagogy, which, in dialogue, build the necessary contribution to the discussion about memory and identity, recognizing the social function of museological and educational activities by promotion of social justice and human development. The object of study presented is the sociopedagogical experience by a differentiated Education in the community of Conceição das Crioulas, located in the city of Salgueiro, state of Pernambuco, northeastern Brazil. It emphasizes the initiative of the community to register their life histories as a way of cultural reconstruction and strengthening of the identity of resistance, in favor of their struggles, primarily the reconquest and protection of their territory. As methodology, was used case study oriented by hypothetical-deductive metod, with a qualitative approach, complemented by the Histories of Life/Narratives biographical methodology. Keywords: Education; Memory; Sociopedagogy; Social Museology; Life Stories; Conceição das Crioulas; Quilombo; Territory; Identity